Senhoras e senhores de terras: redes de sociabilidade e relações de gênero no espaço econômico da Ribeira do Acaraú (Século XVIII) - Magalhães, Leiliane Kecia (2023)
This research aims to analyze the relationships formed by women and men who sought to become landowners and landowners in the Acaraú riverbank, where the Ibiapaba village was located, surrounded by rivers and streams, essential supports for defense, work and livestock farming. It is limited to the first half of the 18th century, when the largest number of lands donated by the Portuguese Crown, the so-called sesmarias, was seen, a period of intense conflicts and continuous negotiations over land ownership. The documentary corpus comprises the Letters of sesmarias and genealogies, for the identification of subjects and established relationships; Portuguese legislation (Philippine Code, Charters and Royal Letters), ecclesiastical guidelines (Council of Trent and the First Constitutions of the Archbishopric of Bahia) and Catholic sermons, which standardized gender relations. As a theoretical contribution, gender studies were used in their relationship with the historical discipline, understanding that the actions of women and men do not occur in isolation and are not standardized passively, since power relations are multiple and unpredictable. In the Acaraú riverbank, it was observed that in the first half of the 18th century there was a movement of women and men coming from different areas, requesting land, carrying out commercial exchanges, involved in political and economic disputes, and to achieve their interests they formed networks of sociability composed of the most diverse subjects (indigenous people, farmers, Jesuits, secular priests, royal agents), resisting the norms of the Catholic church and Portuguese legislation, becoming great ladies and land lords.